Odpowiedzi

2010-02-21T20:03:14+01:00
A]
-6(x²-7y+2)-2(x²-y-12)=
-6x²+42y-12-2x²+2y+24=
-18x²+44y+12
b]
-5x(2x-8y+6)-7(x²-16xy+4x)=
-10x²+40xy-30x-7x²+112xy-28x=
-17x²+152xy-58x
c]
-(8x²-5x+6)-(9x²+6x-12)=
-8x²+5x-6-9x²-6x+12=
-17x²-x+6
  • Użytkownik Zadane
2010-02-21T20:05:26+01:00
A) -6(x²-7y+2)-2(x²-y-12)= -6x² + 42y - 12 - 2x² + 2y + 24 = -18x² + 44y + 12

b) -5x(2x-8y+6)-7(x²-16xy+4x)= -10x² + 40xy - 30x - 7x² + 112xy - 28x = -17x² + 152xy - 58x

c) -(8x²-5x+6)-(9x²+6x-12)= -8x² + 5x - 6 - 9x² - 6x + 12= -17x² -x + 6


2010-02-21T20:07:50+01:00
A).-6x²+42y-12-2x²+2y+24=-8x²+44y+12
b).-10x²+40xy-30x-7x²+112xy-28x=-17x²+152xy-58x
c).-8x²+5x-6-9x²-6x+12=-17x²-1x+6